2021
DOI: 10.1080/23802359.2021.1875912
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete mitochondrial genome of Pentatoma semiannulata (Hemiptera: Pentatomidae)

Abstract: The Pentatoma semiannulata is an important fruit pest in Chinese agricultural system. In current study, the complete mitochondrial genome of P. semiannulata is determined. This mitogenome is 15,515 bp in size and comprises of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a control region. Gene order is identical to that of the putative ancestral arrangement of insects. All protein-coding genes initiate with ATN, except for ATP8, COX1 and NAD1 use GTG or TTG as the start codon, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…In this paper, we describe the mitochondrial genomes of E. rosaceus , E. montivagus , E. gibbosus , E. annamita , and E. ventralis . Similar to that of other hemipteran mitogenomes, the gene arrangements of the five mitochondrial genomes are conserved [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The size of the complete mitogenome sequences varied widely among the examined species, ranging from 15,558 bp in E. gibbosus to 16,043 bp in E. rosaceus ( Table S3 ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this paper, we describe the mitochondrial genomes of E. rosaceus , E. montivagus , E. gibbosus , E. annamita , and E. ventralis . Similar to that of other hemipteran mitogenomes, the gene arrangements of the five mitochondrial genomes are conserved [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The size of the complete mitogenome sequences varied widely among the examined species, ranging from 15,558 bp in E. gibbosus to 16,043 bp in E. rosaceus ( Table S3 ).…”
Section: Discussionmentioning
confidence: 88%
“…The comparison of tandem repeats in the control region seems to be conserved within Eysarcoris , with the exception of E. gibbosus , which had two types of tandem repeat. Previous studies have reported varying sizes and differentiated tandem repetitions in other Pentatomidae species [ 41 , 44 ]. Compared to the varied size of complete mitogenomes, relatively little variation was observed in the length of PCGs, tRNAs, and rRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the phylogenetic relationship between Pentatoma and Plautia was relatively close, and they were far from Graphosoma . However, when the phylogenetic tree was constructed with Pentatoma semiannulata , the relationship between Pentatoma and Graphosoma was closer ( Wang et al 2021 ). Second, the selection of outgroup also affects the topological structure of phylogenetic tree.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the abundance of species in the superfamily, only 97 species have complete or nearly complete mitogenomes published in the National Center for Biotechnology Information (NCBI; https://www.ncbi.nlm.nih.gov/2020.07 ); these represent only eight families. Moreover, there has been no discussion about the phylogenetic position of Pentatoma species, except for the description of Pentatoma semiannulata (Motschulsky) mitogenome by Wang et al (2021) . Therefore, it is necessary to determine more mitogenome sequences of Pentatoma species to better understand its phylogenetic relationships.…”
Section: Introductionmentioning
confidence: 99%